PERGESERAN PERANAN MILITER MASA TRANSISI PEMERINTAHAN INDONESIA (1997-2000) - Makhasuci, Eggi; ', Kamaruddin; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The existence of ABRI in line with its role in Indonesia after the 1980s until the 1990s has gained the spotlight and criticism from various segments of society such as scientists, political experts, intellectuals, public figures and even ABRI's own retired officers. This situation provoked the reaction of the Indonesian people to the role of ABRI so intense and criticized that its role in all life arrangements in Indonesia must be reviewed so as not to suffer the people and the destruction of the Indonesian nation. The purpose of this research is to know the history of the birth of the TNI, to know the role of military transition period of government in politics, to know the role of military transition period of government in economy, to know role of military transition government in social-culture field. And To know the role of Military during the transition of Government in the field of Defense. The method used in this research is historical and qualitative method. Data is collected through literature and decumentation techniques. The data is obtained from books, magazines, and articles in its own analysis. Then dianalis using qualitative descriptive. The result of this research is that there has been a shift in the role of the military during the transition of Indonesian government where in the era of President Soeharto the role of the military still feels strong but after the end of the Soeharto government the role of the military was restored to its original function as a tool of state power in charge of maintaining the sovereignty, Republic of Indonesia.Keywords: Shifting, Military, Government of Indonesia